Elevated system exposures of baicalin after combinatory oral administration of rhein and baicalin: Mainly related to breast cancer resistance protein (ABCG2), not UDP-glucuronosyltransferases. (25th March 2020) - Zhang, Yaqing; Zhang, Mei; Hu, Guangnan; Zhang, Zunjian; Song, Rui
Abstract: Ethnopharmacological relevance: A traditional Chinese medicine (TCM) prescription follows the principle of compatibility ( peiwu ) to achieve the fundamental purpose: to increase efficacy and reduce toxicity. Rhei rhizoma, commonly known as Chinese rhubarb, is the most frequently used herb with Radix Scutellariaee. This classic fixed compatibility is considered for heat-clearing, qi regulation and detoxifying to gain better efficacy and reduce cytotoxicity with respect to unilateral medicine. With this in mind, we propose it is highly promising to find ingredients in rhubarb to increase the bioavailability of baicalin. Aim of study: In the present study, effect of rhien on pharmacokinetic profile of baicalin in rat plasma was investigated, and the underlying mechanisms were partly dissected through intestinal absorption, metabolism and biliary excretion with in vivo, in vitro and in situ assays. Materials and methods: Pharmacokinetic analysis in rats was first performed to provide a general overview of the in vivo exposure of baicalin and rhein after co-administration, while the biliary excretion study provided insight to the effect of rhein on the transport of baicalin from hepatocytes to bile. In vitro incubation and inhibition studies in human/rat liver microsome and human/rat intestinal S9 fraction were conducted to elucidate the role of uridine diphosphate-glucuronosyltransferases (UGTs) on the hepatic and intestinal metabolism of baicalein (the aglycone of baicalin), and to determine whether rhein can affect the UGT-mediated glucuronidation of baicalein. In situ intestinal perfusion study was designed to investigate the effect of rhein on intestinal absorption of baicalin, and breast cancer resistance protein (BCRP) inhibitor was co-perfused as positive control to demonstrate the role of the efflux transporter, while BCRP-MDCK II cell(Madin-Daby canine kidney cell) model was used as an in vitro approach to further confirm the conclusion. Results: The AUC and Cmax of baicalin were increased to 189.93% and 305.73%, respectively, and the clearance of baicalin was significantly decreased from 4.17 ± 2.40 to 1.65 ± 0.79 L/h/kg following oral co-administration of rhein. The AUC of baicalin was markedly increased and the biliary clearance was significantly decreased when baicalin and rhein were co-administered intravenously. The effect of rhein on the glucuronidation of baicalein in various subcellular fractions was examined, and it was found that rhein did not affect the UGT-mediated glucuronidation of baicalein. Results of in situ intestinal perfusion revealed that co-perfusion with Ko143 (a potent BCRP inhibitor) or rhein significantly reduced the cumulative excretion amount of baicalin, from 9.27 ± 2.79 to 2.80 ± 0.97 or 4.84 ± 0.60 nM, respectively. Additionally, the efflux ratio Papp (BL-AP)/Papp (AP-BL) of baicalin in BCRP-MDCK II was decreased significantly in the presence of rhein or Ko143, which meant rhein could inhibit the BCRP-mediated efflux transport of baicalin. Conclusions: These results indicated that rhein can increase the bioavailability of baicalin by inhibiting BCRP-mediated efflux transport of baicalin in enterocytes and hepatocytes rather than by affecting the activity of UGT enzyme. Graphical abstract: Image 1